2007
DOI: 10.1590/s0004-28032007000300003
|View full text |Cite
|
Sign up to set email alerts
|

Resposta à vacinação contra a hepatite B em alcoolistas sem cirrose hepática clinicamente evidente

Abstract: RESUMO -Racional -Alcoolistas têm maior prevalência de infecção pelo Vírus da hepatite B (VHB), o que aumenta os riscos de desenvolverem cirrose hepática e/ou hepatocarcinoma. Objetivo -Avaliar a resposta à vacinação contra o VHB em alcoolistas sem cirrose hepática. Métodos -Foram vacinados 20 homens alcoolistas, com idade média de 46,6 ± 10,9 anos, que bebiam mais de 80 g de etanol por dia, por mais de 10 anos. O grupo controle, 40 homens não-alcoolistas, tinha idade média de 37,8 ± 9,7 anos. Nenhum dos indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
(69 reference statements)
2
3
0
3
Order By: Relevance
“…In this study, the frequency of responders among the patients with active alcoholism was similar to that of the patients in abstinence, and, in response to the conventional scheme, a similar fact was also observed in another previous study (4) . The frequency of response to hepatitis B vaccine was also similar among patients with and without liver cirrhosis, and the positive response in the liver cirrhosis patients was related to the presence of serum anti-HBe.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, the frequency of responders among the patients with active alcoholism was similar to that of the patients in abstinence, and, in response to the conventional scheme, a similar fact was also observed in another previous study (4) . The frequency of response to hepatitis B vaccine was also similar among patients with and without liver cirrhosis, and the positive response in the liver cirrhosis patients was related to the presence of serum anti-HBe.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the only patient who had been laboratorially proven to have been infected by HBV had positive anti-HBe and had anamnestic response. None of the patients who were over 60 years responded to the vaccination and a similar fact had already been verified in a previous study in which alcoholic patients had been vaccinated (4) . This could explain why the mean age of the non responder patients was greater than that of the responders.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A previous meta-analysis in 2002 observed many factors influencing response to hepatitis B vaccine, especially a decrease response to recombinant HBV vaccine at higher ages11, which suggested that earlier vaccination should be prioritized for prevention at the population level. However, in the last decade, numerous emerging reports, which focused on the seroprotection rate of hepatitis B vaccine in adults12131415161718192021222324252627282930313233343536373839404142434445464748, are still inconclusive to immunize what adults are the most appropriate in order to increase the seroprotection rate. Factors influencing immunologic response to hepatitis B vaccine in adults have been inconsistently examined in existing studies.…”
mentioning
confidence: 99%
“…26 Auxiliares e técnicos de enfermagem informaram as menores prevalências de imunizados, 57,7%; entretanto, os mesmos profissionais apresentaram alto percentual de acidentabilidade, 38,0%.…”
unclassified